Character Education for Generation Z: Psychoeducation for Parents on Character Education for Elementary School Students at Itqan Darussalam Foundation, East Aceh - Dedy Surya; Muslem Ibnu (Jurnal Pengabdian West Science, 2024)
This community service effort with the objective of educating parents about character development for Generation Alpha children who attend elementary school at the Itqan Darussalam Foundation in East Aceh. Through the provision of psychoeducation, parents acquired knowledge and understanding of effective methods for fostering responsibility, empathy, and ethical principles in their children, especially in relation to the digital era. The program included interactive conversations and small group sessions to cultivate parental comprehension of the significance of character education. The results suggest a notable enhancement in parents' capacity to steer their children's moral and ethical growth while decreasing excessive dependence on technology. The program effectively established a collaboration between families and schools, thereby enhancing the comprehensive development of Generation Alpha.